2021
DOI: 10.4102/sajhrm.v19i0.1407
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life: Effects on turnover intention and organisational commitment amongst selected South African manufacturing organisations

Abstract: Research purpose:The general objective of this study was to examine the relationship between quality of work life and turnover intention and to see whether organisational commitment mediates the relationship between quality of work life and turnover intention.Motivation for the study: The lack of research on the relationships between quality of work life, turnover intention and organisational commitment make it challenging to gain knowledge on the concepts and what influences it can have to embrace these relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
1
12
0
3
Order By: Relevance
“…This may be related to that when nurses were satisfied with their job, having adequate salaries, proper communication between them and upper management, appropriate feedback mechanisms, no intention to leave and able to balance between work and family life which have effect on total QNWL. This study result is supported by (Yusoff, Rimi, & Meng, 2015) and (Els, Brouwers, & Lodewyk, 2021) who mentioned that staff with presence of quality of nursing work life will be able to satisfy their personal and working need while working in the organization and have no intention to leave the organization .…”
Section: Relation Between Qnwl and Its Dimensionssupporting
confidence: 65%
“…This may be related to that when nurses were satisfied with their job, having adequate salaries, proper communication between them and upper management, appropriate feedback mechanisms, no intention to leave and able to balance between work and family life which have effect on total QNWL. This study result is supported by (Yusoff, Rimi, & Meng, 2015) and (Els, Brouwers, & Lodewyk, 2021) who mentioned that staff with presence of quality of nursing work life will be able to satisfy their personal and working need while working in the organization and have no intention to leave the organization .…”
Section: Relation Between Qnwl and Its Dimensionssupporting
confidence: 65%
“…Talent attraction and retention can be explained by push and pull factors (Bazana & Reddy, 2021). Push factors compel existing employees to consider leaving their place of employment because their commitment wanes (Els et al, 2021), whilst pull factors attract potential employees to an organisation (Hooi & Zahari, 2020). The study confirmed that the organisation offered attractive extrinsic rewards and acquired strong talent.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the second research question, the study found that poor HRM practices resulted in high employee turnover, reduced commitment and weak learning culture (Klinck & Swanepoel, 2019). The high employee turnover caused a loss of institutional memory, which resulted in an inevitable erosion of human-centred competitive advantage (Els et al, 2021). Marshall and Stephenson (2020) found that high turnover creates a sense of insecurity within employees, which negatively affects performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations